Gastric Electrical Stimulation: Role and Clinical Impact on Chronic Nausea and Vomiting - Soliman, Heithem; Gourcerol, Guillaume (Frontiers in Neuroscience, 2022)
Gastric electrical stimulation (GES) is currently used as an alternative treatment for medically refractory gastroparesis. GES has been initially developed to accelerate gastric motility, in order to relieve the symptoms of the patients. Subsequent studies, unfortunately, failed to demonstrate the acceleration of gastric emptying using high-frequency stimulation – low energy stimulation although the technique has shown a clinical impact with a reduction of nausea and vomiting for patients with gastroparesis. The present review details the clinical efficacy of GES in gastroparesis as well as its putative mechanisms of action.